PENGARUH ELECTRONIC WORD OF MOUTH DI MEDIA SOSIAL TIKTOK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE SOMETHINC (Survei pada Followers TikTok @somethincofficial) - Syafira Aninditya, (2022)
Somethinc is a new skincare brand that has become famous and hotly discussed and managed to enter the top 50 Indonesian brands in 2020. Currently, one of the social media that is becoming a trend among the public is TikTok and this opens the potential for the Somethinc skincare brand to utilize social media. TikTok as a medium for spreading electronic word of mouth. This study aims to determine the influence and magnitude of the influence of electronic word of mouth on TikTok social media on purchasing decisions for Somethinc skin care products using the Elaboration Likelihood Model theory. This research uses an explanatory quantitative method with purposive sampling technique and uses data analysis technique of Pearson Product Moment correlation test, linear regression test, coefficient of determination test and hypothesis test using t-test. The results show that there is a fairly strong relationship between electronic word of mouth on TikTok social media with indicators of intensity, opinion valence, as well as content and purchasing decisions with indicators of problem recognition, information seeking, alternative evaluation, purchasing decisions and post-purchase behavior having correlation values. of 0.592. The result of the coefficient of determination shows the magnitude of the influence of electronic word of mouth is 35.1% and is influenced by other factors outside the study. The results shown indicate that it has been accepted and rejected, so it is expected that there will be an influence of electronic news by word of mouth on TikTok social media on purchasing decisions for Somethinc skin care products.